High prevalence of HTLV-1 infection among Japanese immigrants in non-endemic area of Brazil. - Larissa M Bandeira; Silvia N O Uehara; Marcel A Asato; Gabriela S Aguena; Cristiane M Maedo; Nikolas H Benites; Marco A M Puga; Grazielli R Rezende; Carolina M Finotti; Gabriela A Cesar; Tayana S O Tanaka; Vivianne O L Castro; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Human T-lymphotropic virus type 1 (HTLV-1) has worldwide distribution and is considered endemic in many world regions, including southwestern Japan and Brazil. Japanese immigrants and their descendants have a high risk of acquiring this infection due to intense population exchange between Brazil and Japan. OBJECTIVE:This cross-sectional study aimed to estimate the prevalence of HTLV, analyze the main risk factors associated with this infection, identify the main circulating types and subtypes of HTLV in Japanese immigrants and descendants living in Campo Grande-MS (Middle-West Brazil), as well as analyze the phylogenetic relationship among isolates of HTLV. STUDY DESIGN:A total of 219 individuals were interviewed and submitted to blood collection. All collected blood samples were submitted for detection of anti-HTLV-1/2 using the immunoassay ELISA and confirmed by immunoblot method. The proviral DNA of the 14 samples HTLV- 1 positive were genotyped by nucleotide sequencing. RESULTS:The overall prevalence of HTLV-1 was 6.8% (IC 95%: 3,5-10,2). Descriptive analysis of behavioral risk factors showed statistical association between HTLV-1 and age greater than or equal to 45 years. The proviral DNA of HTLV-1 was detected in all HTLV-1 positive samples. Of these, 14 were sequenced and classified as Cosmopolitan subtype, and 50% (7/14) belonged to subgroup A (transcontinental) and 50% (7/14) to the subgroup B (Japanese). CONCLUSION:The high prevalence of HTLV-1 found evidence of the importance of early diagnosis and counseling of individuals infected with HTLV-1 for the control and prevention of the spread of this infection among Japanese immigrants and their descendants in Central Brazil.